The Effect of Financial Performance and ESG Disclosure on Firm Value: Evidence from IDX Score Firms in 2024 - Nabil Maulana; Ario Purdianto; Benny Dhevyanto (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the influence of financial performance and ESG disclosure on firm value for companies listed on the Indonesian Stock Exchange (IDX) that are included in the IDX ESG Score index for the year 2024. Financial performance is indicated by Return on Assets (ROA), firm value is quantified using Tobin's Q, and ESG disclosure is denoted by the ESG score released by IDX. Grounded in agency theory, stakeholder theory, and signaling theory, the study utilises a quantitative associative methodology, drawing on secondary data from annual reports and sustainability reports. A purposive sampling method produced a final sample of 58 companies. Multiple linear regression analysis was applied following classical assumption tests. The findings demonstrate that ROA significantly enhances firm value, whereas ESG disclosure exhibits a favourable albeit statistically minor impact on tobin’s Q. Simultaneously, both variables significantly influence firm value, with an Adjusted R-squared of 13.7%, suggesting that additional factors beyond the model explain the majority of firm value variation. These studies confirm that in the Indonesian capital market, financial performance remains the primary signal for investors, while ESG disclosure functions as a supporting signal not yet fully priced by the market.